The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1039/c5dt03719k
|View full text |Cite
|
Sign up to set email alerts
|

A 2-(2′-hydroxyphenyl)benzothiazole (HBT)–quinoline conjugate: a highly specific fluorescent probe for Hg2+ based on ESIPT and its application in bioimaging

Abstract: A benzothiazole derived chemosensor L has been designed based on the excited-state intramolecular proton transfer (ESIPT) mechanism to afford a fluorescence turn-on response specifically in the presence of Hg(2+) ions over a host of biologically relevant metal ions as well as toxic heavy metal ions. The chemosensor exhibits high sensitivity with the detection limit down to 0.11 μM. The metal binding is supported by (1)H NMR titrations, ESI-MS spectral analysis and substantiated by theoretical calculations usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Likewise, 8‐hydroxyquinoline has been established as an antibacterial, antiseptic, and potential anticancer agent . Recently, 2‐(2′‐hydroxyphenyl)benzothiazole (HBT)–quinoline based probe showed cell membrane permeability and efficiency for detection of Hg 2+ in HeLa cells . In unremitting search of cancer theranostic drugs, our groups have established a set of novel cancer theranostic benzothiazolyl‐quinoline conjugates .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, 8‐hydroxyquinoline has been established as an antibacterial, antiseptic, and potential anticancer agent . Recently, 2‐(2′‐hydroxyphenyl)benzothiazole (HBT)–quinoline based probe showed cell membrane permeability and efficiency for detection of Hg 2+ in HeLa cells . In unremitting search of cancer theranostic drugs, our groups have established a set of novel cancer theranostic benzothiazolyl‐quinoline conjugates .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Recently, 2-(2'hydroxyphenyl)benzothiazole (HBT)-quinoline based probe showed cell membrane permeability and efficiency for detection of Hg 2 + in HeLa cells. [16] In unremitting search of cancer theranostic drugs, our groups have established a set of novel cancer theranostic benzothiazolyl-quinoline conjugates. [17] These benzothiazolylquinoline scaffolds have proven potency and selectivity towards adenosine A 3 receptor; because expression of A 3 receptor is well known in cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and co‐workers reported a fluorescent “turn‐off” sensor towards Cu 2+ with a detection limit of 4.9 nM in pure water at pH 3.5; this sensor was based on benzimidazo[2,1‐a]benz[de]isoquinoline‐7‐one. Bharadwaj and co‐workers developed a fluorescent “turn‐on” probe by covalently attaching 5‐(benzothiazol‐2‐yl)‐4‐hydroxyisophthalaldehyde onto 8‐aminoquinoline; this probe exhibited high sensitivity towards Hg 2+ with a detection limit down to 0.11 μM . Although many elaborate chemosensors with single functions can monitor Hg 2+ or Cu 2+ individually , designing dual‐function fluorescent probes for monitoring Hg 2+ and Cu 2+ is attractive.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that exposure to mercury, even at very low concentrations, leads to various diseases in the digestive system, the nervous system, and especially the neurological system, which makes detection of mercury ions (Hg 2+ ) an attractive research area in the biological field [3,4]. Thus, much attention has been focused on developing new methods to monitor Hg 2+ in biological and environmental samples [5,6,7]. Among various kinds of methods, the fluorescent probe method shows important application value because of its high sensitivity, high selectivity, and low damage to samples [8].…”
Section: Introductionmentioning
confidence: 99%